Bibliometric analysis of published research on pediatric health disparities - Glusman, Jennifer W.; Doherty, Kathryn; Johannes, Kacie E.; Willis, Allison W. (International Journal of Contemporary Pediatrics, 2023)
This study aimed to examine the current evidence in the medical literature on health disparities in the pediatric population. A bibliometric analysis of published research focused on health disparities in pediatric patients was conducted to analyze publication trends. A search of the Scopus database was conducted using keywords that were determined to be appropriate by the authors. This analysis helps determine which pediatric subspecialties may be lacking in health disparity research. A total of 2,380 publications from 1979 to 2021 met the inclusion criteria using the keywords “pediatric health disparities.” The number of articles published increased over the observation period, with 679 published between 2020-2021. When grouped by subspecialty, the majority of articles were associated with general pediatrics, followed by oncology, cardiology, nephrology, endocrinology, gastroenterology, neurology, pulmonology, and urology. When organized by health disparity risk factor or population, socioeconomics was the most common followed by race, urban, gender, rural, mental disability, physical disability, gender identity, religion and sexual orientation. The United States published more articles than any other country. The National Institute of Health has funded the majority of pediatric health disparities research. Pediatrics was found to be the leading journal of pediatric health disparity research. Research on pediatric health disparities is most frequently published in the United States, and is most focused on socioeconomics in a primary care setting. There is a large gap of research conducted in pediatric subspecialties, and on health disparities such as religion, sexual orientation, gender, and gender identity.